Shari’ah governance for Islamic capital market: a step forward - Kasim, Nawal; Htay, Sheila Nu Nu; Salman, Syed Ahmed (Contemporary Research Center Australia, 2013)
Since the last few decades, Islamic finance industry has developed tremendously penetrating not only the Muslim countries but surprisingly the non-Muslim countries as well. It has been acknowledged by the scholars on the need for this development to cater for the Islamic banking, Takaful and Islamic capital market industries. These three main industries are interrelated and dependent on each other in order to ensure that the whole Islamic financial system is in compliance with the Islamic principles. Among these three streams of the service industry, the Islamic capital market plays a crucial role to support the other two. Since Islamic banks and Takaful operators have to invest to provide the benefits to the investors and policy holders which are compatible with the conventional counterparts, the Islamic capital market is assumed to be the backbone for the two to survive and grow in the Islamic finance industry. Country such as Malaysia has issued the Shari’ah Governance Framework (SGF) specifically for Islamic banking sector in its most recent development. Since the framework does not cover Islamic capital market, it is the objective of this paper to investigate on the need for a similar requirement to have a comprehensive Shari’ah governance framework for Islamic capital market.